Marginal abatement cost curves in general equilibrium: The influence of world energy prices - Gernot Klepper; Sonja Peterson (Fondazione Eni Enrico Mattei (FEEM), 2004)
Marginal abatement cost curves (MACCs) are one of the favorite instruments to analyze the impacts of the implementation of the Kyoto Protocol and emissions trading. As shown in this paper one important factor that influences MACCs are energy prices. This leads to the question of how to define MACCs in a general equilibrium context where the overall abatement level world wide influences energy prices and thus national MACCs. We first discuss the mechanisms theoretically and then use the CGE model DART to quantify the effects. The result is, that changes in energy prices resulting from different world wide abatement levels do indeed affect the national MACCs. Also, we compare different possibilities of defining MACCs - of which some turn out to be robust against changes in energy prices while others vary considerably.
Keywords: C68; D58; F18; Q41; 330; Marginal abatement cost; Energy price; Computable general equilibrium model; Climate change; Klimaschutz; Klimaveränderung; Umweltschutzkosten; Erdölpreis; Allgemeines Gleichgewicht; Simulation; Welt